Liquid-state carbon-13 hyperpolarization generated in an MRI system for fast imaging - Schmidt, A. B. (Nat Commun, 2017)
Hyperpolarized (HP) tracers dramatically increase the sensitivity of magnetic resonance imaging (MRI) to monitor metabolism non-invasively and in vivo. Their production, however, requires an extra polarizing device (polarizer) whose complexity, operation and cost can exceed that of an MRI system itself. Furthermore, the lifetime of HP tracers is short and some of the enhancement is lost during transfer to the application site. Here, we present the production of HP tracers in water without an external polarizer: by Synthesis Amid the Magnet Bore, A Dramatically Enhanced Nuclear Alignment (SAMBADENA) is achieved within seconds, corresponding to a hyperpolarization of ∼20%. As transfer of the tracer is no longer required, SAMBADENA may permit a higher polarization at the time of detection at a fraction of the cost and complexity of external polarizers. This development is particularly promising in light of the recently extended portfolio of biomedically relevant para-hydrogen-tracers and may lead to new diagnostic applications.